Self-Adjustment of Truant Students In Vocational High School 5 Padang - Yunisa Handaramon; Syahniar Syahniar; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
This study aims to describe the truism of students who are truant in terms of the adjustment of students with peers, and adjustment of the teacher in learning. The method in this research is quantitative descriptive with 36 research subjects who play truant in SMK Negeri 5 Padang. The instrument used is a Likert scale. Data were analyzed using percentage techniques. The findings of the study show (1) the adjustment of students who play truant in terms of the adjustment of students to peers at school is generally classified as low (50%), (2) the adjustment of students who play truant in terms of students' adaptation to teachers in learning in general is very low (83.3%), (3) overall in the low category (83.3%). The results of this study can be used as a reference in making programs for counseling teachers or counselors so that students' adaptation can be developed positively.